Improving Social Science Learning Outcomes of Class V Elementary School Students through the TPACK Approach - Desak Made Darmawati; Nur Busyra; Ervin Azhar (Al Ibtida: Jurnal Pendidikan Guru MI)
The main problem in this study is the low learning outcomes of fifth grade students in social studies at a private elementary school in East Jakarta, Indonesia. This is because the learning approach used in these schools is still conventional. The purpose of this study was to improve social studies learning outcomes for fifth grade students using the technology pedagogical content knowledge (TPACK) approach. By using classroom action research, this research was conducted in three cycles involving 10 students. Each cycle consists of planning, implementing, acting, observing, and reflecting. Data collection was carried out using a test consisting of a pre-test and post-test. The test results data were then analyzed using descriptive statistics. The results showed that based on the post-test results in cycle I, only 6 students or 60% fulfilled the KKM. In cycle II the percentage of student learning completeness increased to 70% or 7 students fulfilled the KKM. In cycle III, student learning completeness again increased to 82%. Therefore, it can be concluded that the use of the technology pedagogical content knowledge (TPACK) approach in social studies learning is effective in improving student learning outcomes.